Determinants of the Information Disclosure on ERM Practices - Evidence from Portugal and the United Kingdom - Pinto, C.R.A.A.; Azevedo, G.; Oliveira, J. (18th Grudis Conference, 2019)
The empirical study was carried out to identify the determinants of the disclosure level on ERM practices by fifty-two non-financial companies listed on Euronext Lisbon (EL) and London Stock Exchange (LSE), between 2006 and 2016. Using the content analysis technique on annual reports, corporate governance reports and sustainability reports, and based on the COSO Enterprise Risk Management – Integrated Framework, we made the quantification of information disclosure on ERM. The results allowed us to conclude that variables as “board of directors size”, “CEO and Chairman duality”, “gender diversity of the board of directors”, “management compensation”, “audit committee independence”, “audit committee meetings” and “internationalization level” have a significant influence on the level of information disclosure on ERM practices experienced by EL and LSE non-financial companies.